2012
DOI: 10.1111/j.1365-3083.2012.02671.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Reference Values for the Peripheral T cell Compartment

Abstract: Immunophenotyping of blood lymphocyte subpopulations is an important tool in the diagnosis of immunological and haematological diseases. Paediatric age‐matched reference values have been determined for the major lymphocyte populations, but reliable reference values for the more recently described T lymphocyte subpopulations, like different types of memory T lymphocytes, recent thymic emigrants, regulatory T cells and CXCR5+ helper T lymphocytes, are not sufficiently available yet. We determined reference value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
145
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 24 publications
21
145
4
3
Order By: Relevance
“…34 Potentially, various patient/donor-dependent variables such as weight, lymphocyte count prior to UCBT, and age influence ATG PK and pharmacodynamics (PD). 35 Further improving outcome after UCBT may therefore require a more individualized approach to ATG timing and dose adapted to indication, immunologic status, and infectious comorbidities of the patient. This can possibly be achieved by implementing PK/PD modeling techniques for antibody agents such as ATG.…”
Section: Discussionmentioning
confidence: 99%
“…34 Potentially, various patient/donor-dependent variables such as weight, lymphocyte count prior to UCBT, and age influence ATG PK and pharmacodynamics (PD). 35 Further improving outcome after UCBT may therefore require a more individualized approach to ATG timing and dose adapted to indication, immunologic status, and infectious comorbidities of the patient. This can possibly be achieved by implementing PK/PD modeling techniques for antibody agents such as ATG.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte subset distributions by age are reported in Table 1 (percentages) and Table 2 (absolute counts 310 9 /L), which also list WBC and lymphocyte values. We tabulated the 10th and 90th percentiles, in addition to 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) …”
Section: Resultsmentioning
confidence: 99%
“…Changes in antibody production are the hallmark of various human B-cell deficiencies, known as primary antibody deficiencies (PADs); these conditions are the most common primary immunodeficiencies (PIDs) (5). Some studies (1,2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) have demonstrated that age, sex, race, geographic area, and nutritional status can influence variation in Department of Clinical Laboratory, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, China lymphocyte subsets, and undernutrition due to insufficient intake of energy and macronutrients and/or due to deficiencies in specific micronutrients can impair the immune system, such as suppressing immune functions that are fundamental to host protection (20), which could in turn influence the distribution of different lymphocyte subsets. Normally, the immune system is functionally immature at birth, and it undergoes sequential development that is genetically determined and additionally stimulated by antigen exposure (21).…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы, у здоровых детей в возрастном интервале от 1 года до 16 лет со-отношение основных субпопуляций среди Т-лимфоцитов крови изменяется незначи-тельно и практически соответствует показате-лям у взрослых здоровых доноров [11,25]. Эти сведения дают возможность сопоставить от-носительное содержание субпопуляций лим-фоцитов у детей в возрасте от 1 года до 16 лет, переносящих вирусные или бактериальные менингиты (табл.…”
Section: результатыunclassified